Expression and epitope prediction of MPT64 recombinant proteins from clinical isolates of Mycobacterium tuberculosis as immunoserodiagnostic candidates - Fihiruddin, Fihiruddin; Inayati, Nurul; Jannah, Raudatul; Unsunnidhal, Lalu; Kusumawati, Asmarani (Veterinary World, 2022)
Background and Aim: The success in the handling and prevention of tuberculosis (TB) cases is highly dependent on their rapid detection, monitoring, and treatment. The efficacy of the Bacille Calmette–Guerin (BCG) vaccine is inconclusive in eastern Indonesia. The RV1980c gene of Mycobacterium tuberculosis encodes an antigenic protein that is considered to be a virulence factor, as it can stimulate the immune response in patients with TB. This study aimed to study the expression and epitope indicator of MPT64 recombinant proteins from clinical isolates of M. tuberculosis as immunoserodiagnostic candidates for pET SUMO plasmids from clinical isolates as candidates for serodiagnostic tests and recombinant vaccines. Materials and Methods: The polymerase chain reaction (PCR) product of the RV1980c gene was inserted into the SUMO pET plasmid, which was then transformed into Escherichia coli BL21 (DE3) cells and expressed in Luria Bertani media induced by 1.0 M IPTG. Subsequently, sequencing was performed and the results were analyzed using the ClustalW and National Center for Biotechnology Information BLAST software. The T-cell epitope prognosis was then explained by GENETYX version 8.0., for the prediction of B-cell epitope, as assessed using an Immune Epitope Database analysis. Results: The PCR product of the RV1980c gene had a length of 619 bp. Moreover, SDS– polyacrylamide gel electrophoresis and Western blotting revealed that the protein encoded by the Rv1980c gene weighed 36 kDa. We gained nine specific T-cell epitopes according to Iad Pattern position and eight epitopes according to Rothbard/Taylor Pattern Position; furthermore, we detected five B-cell epitopes in the RV1980c gene. Conclusion: The MPT64 protein encoded by the RV1980c gene carries epitopes that are realized by lymphocytes and represent potential immunoserodiagnostic candidates in diagnostic immunology.